Developing teaching material design of basic English Vocabulary based on interactive multimedia for Elementary School - Abdullah; Seny Luhriyani Sunusi; Bilal Ahmad Bhat (International Journal of Humanities and Innovation (IJHI), 2021)
Teaching English vocabulary to children in the classroom should begin as early as possible because childhood is a golden age when everything may be absorbed simply and rapidly. Language holds the belief that the earlier children learn a foreign language, the easier it is for them to master it, and that children may learn a language more quickly and with less difficulty than adults. This research aims to develop a learning design instructional material model of basic English Vocabulary based on interactive multimedia for elementary students and to increase knowledge and skills of language, especially for elementary school students. Development of learning model and instructional material design followed a research design and development model designed. This research is an extensive process in designing the students' needs and develop the product or course material of basic English vocabulary to increase the ability or skills of elementary students in learning language through interactive multimedia. The sample of this research is the students at one of the elementary schools in Makassar, South Sulawesi, Indonesia. The research showed a learning model based on the interactive multimedia syllabus and instructional material design of basic English Vocabulary. The researchers suggested that formative assessment be undertaken each time the materials are delivered to determine which components should be modified to increase the materials' instructional and motivating value. Furthermore, summative evaluation should be carried out in order to make a policy decision on whether or not to use instructional materials based on real evidence of their success.